Predatory Conduct under the Commerce Act 1986 - Coull, David (Victoria University of Wellington Law Review, 1998)
This article examines the significance of the Court of Appeal's decision in Commerce Commission v Port Nelson Limited. The Court's analysis of predatory pricing, "bundling" and the tug tie is explored. The article concludes that the effect of the Court of Appeal's decision is to significantly widen the scope of section 27 of the Commerce Act. This is contrasted with the restrictive interpretation that recent courts have accorded section 36. The article concludes that court decisions have fundamentally changed the scheme of the Commerce Act 1986.